2022
DOI: 10.1177/20552076221085070
|View full text |Cite
|
Sign up to set email alerts
|

The importance of social media users’ responses in tackling digital COVID-19 misinformation in Africa

Abstract: Objective Digital technologies present both an opportunity and a threat for advancing public health. At a time of pandemic, social media has become a tool for the rapid spread of misinformation. Mitigating the impacts of misinformation is particularly acute across Africa, where WhatsApp and other forms of social media dominate, and where the dual threats of misinformation and COVID-19 threaten lives and livelihoods. Given the scale of the problem within Africa, we set out to understand (i) the potential harm t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Thence, society, stakeholders, governments, as well as the general populace must make and consider choices that are mindful and intentional concerning the manner of leveraging technology that can help enhance lives, mitigate stress as well as improve mental health. Imperatively, individuals should reduce the recurring exposure to what the media projects about the pandemic alongside accompanying social activities that trigger distress [27], be cautious about social media usage from a high-level perspective [29,93], and avoid overload of work which may lead to psychological and mental health challenges [28]. With all the drawbacks being revealed from the literature, technology benefits are leveraged to enhance accessibility across a diversity of socioeconomic groups, thus ensuring the positive impact of technology is equally dispersed in society.…”
Section: Recommendations and Conclusionmentioning
confidence: 99%
“…Thence, society, stakeholders, governments, as well as the general populace must make and consider choices that are mindful and intentional concerning the manner of leveraging technology that can help enhance lives, mitigate stress as well as improve mental health. Imperatively, individuals should reduce the recurring exposure to what the media projects about the pandemic alongside accompanying social activities that trigger distress [27], be cautious about social media usage from a high-level perspective [29,93], and avoid overload of work which may lead to psychological and mental health challenges [28]. With all the drawbacks being revealed from the literature, technology benefits are leveraged to enhance accessibility across a diversity of socioeconomic groups, thus ensuring the positive impact of technology is equally dispersed in society.…”
Section: Recommendations and Conclusionmentioning
confidence: 99%
“…Globally applicable infodemic measurements and metrics are needed. The true cost of infodemics has not been robustly measured but has been anecdotally reported, with impacts such as stigma, violence against health workers, overdoses of nonrecommended treatments or stockouts, refusal by individuals or communities to wear masks or get vaccinated, and frivolous lawsuits against health systems and health care workers [ 15 ]. One academic brief suggested that COVID-19 misinformation cost US $50-$300 million a day at the height of the pandemic in the United States [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“… 9 The phenomenon exacerbated the spread of misinformation on COVID-19 diagnosis, treatment, preventive measures, 7 , 9 and conspiracy theories. 10 As a result, the navigation of COVID-19 information became increasingly complex and challenging, raising concerns about anxiety, 11 and the well-being of students who often spent a large amount of time exposed to digital content, 9 , 12 , 15 leading to feelings of confusion and stress. 9 , 16 Pramukti et al showed receiving more information regarding COVID-19 significantly increased the level of anxiety among Taiwanese students.…”
Section: Introductionmentioning
confidence: 99%